(untitled) (European Journal of Behavioral Sciences, 2020)
This study is concerned with highlighting the effect of vocal processing skills of vocal awareness and vocal working memory on the development of reading mechanisms and difficulties. The study was conducted on a total sample of 280 male and female pupils in the third, fourth and fifth phases of primary school ages 8-11, among them 50 children with dyslexia who were diagnosed according to a battery of standards that the researcher prepared for this purpose and that respond to the standards Psychometrics to build tests. The study aims to: To ensure the effectiveness of a pedagogical treatment program in developing reading skills for students with dyslexia dependent on phonological awareness activities and phonological working memory and the transition from part to whole gradually. In general, children with dyslexia suffer from a great and persistent difficulty in phonemic representation, in addition to a deficiency in the lower linguistic units in the Arabic language and their use to reach the skills of recognizing the written word by linking between the linear phonemic compatibility of the voice. Our findings support the evolutionary hypothesis of general disability in vocal processing skills and concluded that rhyme awareness appears before vocal syllabic awareness. A child at this level finds difficulty in phonograms with moving sound. Additionally, multiple regression analysis shows that poor vocal memory is the best indication of poor vocal awareness in the Arabic language. Studies also focused on the effectiveness of the proposed program for the treatment of vocal dyslexia in improving the ability to read in general.